Optimal design of three-phase solar PV integrated unified power quality conditioner (UPQC) - Yogesh S. Pawar; Mahesh Kadu; Pawan C. Tapre; Dinesh S. Wankhede; Rajendra M. Rewatkar; Swapna M. Choudhary; Rakesh G. Shriwastava (International Journal of Applied Power Engineering (IJAPE), 2026)
This research investigates the utilization of a unified power quality conditioner (UPQC) to address power quality issues in the electrical grid and mitigate harmonics introduced by non-linear loads. The UPQC system is augmented by a combination of photovoltaic (PV) and battery energy storage system (BESS). Typically, the PV system supplies active power to the load. However, in cases where the PV system cannot provide sufficient power, the BESS is activated to ensure a continuous power supply, particularly during prolonged voltage interruptions. To enhance system reliability and reduce dependency on environmental conditions, a hybrid PV-BESS system is proposed. The inclusion of the BESS improves long-term voltage support capabilities, simplifies the DC-link voltage regulation algorithm, and facilitates the production of clean energy. For efficient phase synchronization operation of the UPQC controller under unbalanced and distorted grid voltage conditions, a self-tuning filter (STF) integrated with the unit vector generator (UVG) technique is employed.